FORMULATION, SENSORY EVALUATION, BIOACTIVE COMPOUNDS, ANTIOXIDANT ACTIVITY, AND ALPHA-GLUCOSIDASE INHIBITION OF FUNCTIONAL INFUSION BEVERAGE FROM MACE AND NUTMEG SEEDS (MYRISTICA ARGENTEA WARB.) - Maryati; Kuliahsari, Dessy Eka (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2025)
Functional tea bags containing mace and nutmeg (Myristica argentea Warb.) were developed to support blood glucose regulation amid the rising prevalence of degenerative diseases, including diabetes mellitus, in Indonesia. Both ingredients contain bioactive compounds such as flavonoids, myristicin, and phenolic acids that may contribute to glucose regulation. This study evaluated the effect of varying mace and nutmeg proportions on sensory acceptance, determined the optimal formulation, and assessed bioactive properties, antioxidant activity, and alpha glucosidase inhibitory potential. A one-factor Completely Randomized Design (CRD) was applied with four formulations: F1 (0.05 g : 0.25 g), F2 (0.10 g : 0.20 g), F3 (0.15 g : 0.15 g), and F4 (0.20 g : 0.10 g). Sensory evaluation used a seven-point hedonic scale for color, aroma, taste, and aftertaste, analyzed by chi-square and Duncan’s Multiple Range Test (DMRT) if a 5% significance level. The optimal formulation was determined using the De Garmo method. Results showed that varying proportions significantly affected all sensory parameters. F2 (0.10 g : 0.20 g) achieved the highest scores: color 5.98, aroma 6.51, taste 6.40, and aftertaste 6.00. Its bioactive profile included total phenolics of 20.91 mg GAE/g, total flavonoids of 0.3 mg QE/g, and antioxidant activity with an IC50 of 448.78 ppm (weak). F2 also showed increasing alpha-glucosidase inhibition with rising concentrations, reaching 31.56 % at 100,000 ppm. These findings indicate that F2 exhibits low alpha glucosidase inhibitory activity due to its limited phenolic and flavonoid content, highlighting the need for formulation and extraction optimization to enhance the bioactive compound levels and the functional potential of mace–nutmeg tea bags in a herbal jamu preparation.